Antifungal prophylaxis of patients undergoing allogenetic hematopoietic stem cell transplantation in China: a multicenter prospective observational study. Issue 1 (December 2016) - Gao, Lei; Sun, Yuqian; Meng, Fanyi; Han, Mingzhe; Huang, He; Wu, Depei; Yu, Li; Ren, Hanyun; Huang, Xiaojun; Zhang, Xi
Abstract Background Antifungal prophylaxis is currently regarded as the gold standard in situations with allo-genetic hematopoietic stem cell transplantation (allo-HSCT). However, the epidemiological information regarding prophylaxis of invasive fungal diseases (IFDs) is not clear in China. Methods We report the first large-scale (1053 patients) observational study of the prophylaxis and management of IFDs among patients with allo-HSCT in China. Results The incidence rates of IFD after primary antifungal prophylaxis (PAP), secondary antifungal prophylaxis (SAP), and non-prophylaxis were 22.7 vs. 38.6 vs. 68.6 %, respectively (P  = 0.0000). The median time from transplantation to IFD was 45 days in PAP patients, 18 days in SAP patients, and 12 days in non-prophylaxis patients.Aspergillus spp . represents the most common type of fungal infection. Independent risk factors for IFD in allo-HSCT patients with PAP were age, having human leukocyte antigen (HLA)-haploidentical or matched unrelated donor, decreased albumin levels, and the use of itraconazole as the prophylactic antifungal agent. Among SAP transplant recipients, there was no significant risk factor for IFDs. The incidence rates of overall survival (OS) in the PAP, SAP, and no prophylaxis groups were 85.07, 78.80, and 74.82, respectively (P  = 0.01). Conclusions This observational study indicates that prophylaxis of IFD is helpful to reduce the incidence of IFDs and improve the OS of patients after allo-HSCT.